The impact of biologic agents on health-related quality of life outcomes in patients with psoriasis. (2nd January 2018) - Frieder, Jillian; Kivelevitch, Dario; Fiore, Connie Tran; Saad, Saadeddine; Menter, Alan
ABSTRACT: Introduction : Psoriasis is a common, immune-mediated skin disease often associated with significant physical and psychosocial impairment. Antipsoriatic biologic agents offer patients unparalleled treatment potential in regard to greater skin clearance and overall improved quality of life. Evaluation of the therapeutic efficacy of biologic agents on the full psoriasis disease burden must account for their impact on both physical symptoms, as well as patient-reported, health-related quality of life (HRQoL) measurements. Areas covered : Results from numerous clinical trials demonstrate the significant clinical efficacy of biological agents targeting tumor necrosis factor-α (TNF-α) and the interleukin (IL)-12/23 and IL-17 immune pathways. However, relatively limited data is available evaluating their full effect on quality of life outcomes. This review will discuss the most relevant and up-to-date clinical data on HRQoL measurements related to treatment with these aforementioned biologic agents. Expert commentary : Patient-reported outcomes (i.e. Dermatology Life Quality Index) are being used with increasing frequency in clinical trials, and provide valuable information on the impact of psoriasis on numerous aspects of day-to-day living. These outcomes must also be incorporated in clinical practice, in addition to physical assessment of disease severity, treatment decisions, and therapeutic response in the psoriasis patient population.